Robust optimization of air based relay for internet of things based on UAV - Wei WANG; Renqian GU; Li3 PENG; Jijun ZHAO; Zhongcheng WEI; Cunxi CHANG (物联网学报)
Faced with the need of key regional information transmission in the emergency situation where the perception network lacks of ground base stations, considered about the uncertainty of spatial positioning of emergency internet of things (eIoT) nodes, a robust optimization method for air-based relay of eIoT based on unmanned aerial vehicle (UAV) was proposed.Firstly, the system modeling of this kind of eIoT was carried out.Secondly, according to the fact that the non-convex and nonlinear model has a great correlation with the positioning accuracy of the ground-based eIoT equipment and the tiny disturbance of the positioning information can lead to the invalid solution of the model, the system model was relaxed and the uncertainty description of the location data of the eIoT equipment was introduced, Then the robust equivalent model of the low altitude UAV relay communication power optimization problem was obtained.Thirdly, the model solving algorithm was given.Finally, the effectiveness and robustness of the proposed method were verified from the deployment of UAV and communication energy consumption.At the same time, the factors effecting the effectiveness of the proposed method were analyzed.